Metallicity Mapping of the Ionized Diffuse Gas at the Milky Way Disk–Halo Interface - Bo-Eun Choi; Jessica K. Werk; Kirill Tchernyshyov; J. Xavier Prochaska; Yong Zheng; Mary E. Putman; Drummond B. Fielding; Jay Strader (The Astrophysical Journal)
Metals in the diffuse, ionized gas at the boundary between the Milky Way’s interstellar medium (ISM) and circumgalactic medium, known as the disk–halo interface (DHI), are valuable tracers of the feedback processes that drive the Galactic fountain. However, metallicity measurements in this region are challenging due to obscuration by the Milky Way ISM and uncertain ionization corrections that affect the total hydrogen column density. In this work, we constrain ionization corrections to neutral hydrogen column densities using precisely measured electron column densities from the dispersion measures of pulsars that lie in the same globular clusters as UV-bright targets with high-resolution absorption spectroscopy. We address the blending of absorption lines with the ISM by jointly fitting Voigt profiles to all absorption components. We present our metallicity estimates for the DHI of the Milky Way based on detailed photoionization modeling of the absorption from ionized metal lines and ionization-corrected total hydrogen columns. Generally, the gas clouds show a large scatter in metallicity, ranging between 0.04 and 3.2 Z _⊙ , implying that the DHI consists of a mixture of gaseous structures having multiple origins. We estimate the inflow and outflow timescales of the DHI ionized clouds to be 6–35 Myr. We report the detection of an infalling cloud with supersolar metallicity that suggests a Galactic fountain mechanism, whereas at least one low-metallicity outflowing cloud ( Z < 0.1 Z _⊙ ) poses a challenge for Galactic fountain and feedback models.